Students' attitudes towards mathematics in lower grades as an element of motivation for learning - Kovács Elvira I.; Maričić Sanja M. (University of Kragujevac - Faculty of Pedagogy, Užice, 2023)
An important condition for effective teaching in mathematics is the attitude of students towards the subject. Our research seeks to answer the question as to what attitudes students have towards mathematics by examining three elements: emotional (affective) relations, intellectual (cognitive) stimulation and moral (effective) parameters. We have examined a total of 364 pupils in the lower grades of the primary schools. The research is based on the method of scaling. Students have been asked questions in order to find out which factors have the strongest influence on their motivation to learn mathematics. The results show that students have positive attitude towards mathematics and they have good relationship with the teacher. The research demonstrated that motivation to learn mathematics is most strongly influenced by emotional and moral impact, followed by intellectual impact. Within the dimensions, the most intense effects are represented by anxiety, the interesting nature of the lessons, relationship with the teacher, and attachment to mathematics as a subject. The results have implications for developing a broader understanding of the nature of students' motivation to learn mathematics and for improving their engagement in mathematics learning.